Ocorrência de novos elementos megaflorísticos na Bacia Carbonífera do Douro (Estefaniano C inferior) [Gzheliano inferior], NW de Portugal - P. Correia (2010)
New megafloristic elements were found in the São Pedro da Cova region (Gondomar), Douro Basin (lower Stephanian C) [lower Gzhelian]